Racial Perception in Me and White Supremacy and When They Call You a Terrorist, A Black Lives Matter Memoir - James, Gitonga; Mate, Antony Mukasa (International Journal of Research in Interdisciplinary Studies, 2024)
African American literature has been greatly shaped by racial themes, hence understanding the experiences of people of colour is essential for grasping the current situation in the United States. Memoirs like When They Call You a Terrorist; A Black Lives Matter Memoir and Me and White Supremacy are important for exploring identity and offering new insights into race relations and cultural conflicts. This paper looks at how racial perceptions are depicted in Me and White Supremacy by Layla F. Saad, and When They Call You a Terrorist; A Black Lives Matter Memoir by Patrisse Khan-Cullors and Asha Bandele. The main argument is that people of colour often face racial marginalization, leading to their identities being appropriated by more powerful social groups. This study uses the idea of orientalism from postcolonial theory to explore the challenges of racial ambivalence. It argues that in the context of racial conflict, cultural stereotypes often fuel both discrimination and oppression.